PERFORMANCE EVALUATION OF TENSION ONLY BRACED FRAME - Iga Maura, Fauziyah
In accordance with SNI 1726-2019, the tension only braced frame (ToBF) structure can be used as a seismic force-resisting system for seismic design category A to C, with a height exceeds 10 m. The values of R, Cd and ?o for similar structures are not provided in the code, but previous studies reccomended to use R = 3 and ?o = 2 for such structures. The parameters that used in this study is R = 3.25, ?o = 2 and Cd = 3.25. The study of ToBF structures will be done for buildings in seismic design category D with various stories, that is 3 floors (10.5 m), 8 floors (28 m) and 15 floors (52.5 m) to find out whether the building height that exceeds the 10 m can be designed to satisfy the requirements of SNI 1726-2019 and to determine the performance of the structure ToBF in low, medium and high buildings. The analysis that will be used is modal response spectrum (MRSA) for the design of the building structure, then the design were evaluated using linear response history analysis (LRHA) to determine the axial force of the braces and the interstory drift, and pushover analysis were conducted to determine the performance level of the structure. Based on the analysis, the structural design can be carried out for the three ToBF structural models using MRSA and these design satisfy the requirements of SNI 1726-2019. Next, the ToBF structures obtained using MRSA were evaluated using LRHA, and the results show that the requirements were not satisfied in terms terms of capacity and inter-story drift for building structures with that exceed 10 m in height. The designs obtained from the MRSA when reviewed for their performances using pushover analysis according to ASCE 41-13 indicate that the performance level of all buildings is Immediate Occupancy. However, for building structures with a height exceeding 10 m, first yielding occurs at a lower base shear force than the design base shear. This shows that the value of R used is still not adequate. Further review regarding the inter-story drift, the performance level of the elements, and the sequence of plastic hinges development reveals that the ToBF can be used as a seismic force-resisting system. However, the value of R used for ToBF is recommended to be smaller than OCBF (R= 3.25) so that the first yielding occurs at the same or higher base shear force than the design.